Astragali radix (Huangqi): a time-honored nourishing herbal medicine - Yuyu Zhang; Zhejie Chen; Liping Chen; Qin Dong; Dong-Hua Yang; Qi Zhang; Jing Zeng; Yang Wang; Xiao Liu; Yuan Cui; Minglong Li; Xiao Luo; et al. (BMC, 2024)
Abstract Astragali radix (AR, namded Huangqi in Chinese) is the dried root of Astragalus membranaceus (Fisch.) Bge. var. mongholicus (Bge.) Hsiao or Astragalus membranaceus (Fisch.) Bge. As a widely used ethnomedicine, the biological activities of AR include immunomodulatory, anti-hyperglycemic, anti-oxidant, anti-aging, anti-inflammatory, anti-viral, anti-tumor, cardioprotective, and anti-diabetic effects, with minimum side effects. Currently, it is known that polysaccharides, saponins, and flavonoids are the indispensable components of AR. In this review, we will elaborate the research advancements of AR on ethnobotany, ethnopharmacological practices, phytochemicals, pharmacological activities, clinical uses, quality control, production developments, and toxicology. The information is expected to assist clinicians and scientists in developing useful therapeutic medicines with minimal systemic side effects.